The Secret of the Oath (Qasam) in the Al-Qur'an Juz 29 & 30 and its Relevance to Life Values - Muhammad, Pauzi; Waehama, Muhammad Roflee (UIN Sunan Gunung Djati Bandung, 2025)
The purpose of this study is to find out how the secret of oaths and their relevance to life values. Qasam in the Qur'an contained in juz 29 & 30, found as many as 18 surahs spread across 48 verses, in juz 29 there are 10 verses out of 5 surahs, and in juz 30 there are 38 verses out of 13 surahs. Of all the qasam verses that are collected from the oath of Allah are classified into 5 categories, including the oath of Allah with angels, celestial bodies, earth creatures, time and place, while in juz 29 it is found that one oath of Allah with the recitation of aiman and the one who is used as the muqsam bih is a polytheist, the oath of Allah in the Qur'an has secrets and important values, including the oath of Allah shows the majesty of the creator, affirmation and reinforcement conveyed.